2019
DOI: 10.3126/saarctb.v17i1.25025
|View full text |Cite
|
Sign up to set email alerts
|

HIV Vulnerability and Sexual Risk Behaviour of the Drayang Girls in Bhutan

Abstract: Introduction: The rapid socio-economic development in Bhutan has brought changes in individual lifestyles resulting in increased risk behavior of the urban population, particularly the Drayang girls. This study investigated the underlying factors influencing the sexual risk behaviour of Drayang girls and their vulnerability to HIV and Sexually Transmitted Infection (STI). The Drayangs are dance bars in Bhutan where the women perform Bhutanese songs/dances on the stage to entertain the bar patrons and making th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…As exhibited in this study, the heterosexual contact with a female sex worker was consistent with the results of several past national studies where the prevalence of female sex workers and high multiple sexual relationships with low condom use were reported [ 5 , 22 , 23 ]. The 2019 population size estimation (PSE) study also depicted higher sexual partners among women acknowledging sex work, with a mean of 5.8 and 4.5 for female sex workers recruited outside of venues and at venues, respectively, as compared to 1.3 for high-risk women not engaging in sex work.…”
Section: Discussionsupporting
confidence: 92%
“…As exhibited in this study, the heterosexual contact with a female sex worker was consistent with the results of several past national studies where the prevalence of female sex workers and high multiple sexual relationships with low condom use were reported [ 5 , 22 , 23 ]. The 2019 population size estimation (PSE) study also depicted higher sexual partners among women acknowledging sex work, with a mean of 5.8 and 4.5 for female sex workers recruited outside of venues and at venues, respectively, as compared to 1.3 for high-risk women not engaging in sex work.…”
Section: Discussionsupporting
confidence: 92%
“…One study among drayang women found that those who consumed alcohol regardless of prohibition were more likely to engage in transactional sex than those reporting no alcohol consumption. 9 Female sex workers directly recruited at entertainment venues also report higher participation in prevention programs, such as STD testing, health education presentations, and outreach worker contact. Although more than four-fifths of FSW recruited by peers also report recent venue attendance, opportunities to engage them may be fewer compared with employees.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 These venues include bars, karaoke clubs, and the unique Bhutanese entertainment locales called drayangs. [9][10][11] Drayangs are bars where women are hired to perform songs and dances on stage. By conversing with patrons, they obtain "sponsors" to pay for performances.…”
mentioning
confidence: 99%
See 2 more Smart Citations